The Economic (Not Literary) Offenses of Michael Lewis: The Case of The Big Short and the Global Financial Crisis. Issue 4 (9th December 2020) - Chew, Don
Abstract : In a shameless abuse of editorial prerogative, the editor of this journal uses Lewis's bestseller as a pretext and occasion for presenting his own theory of the cause of the global financial crisis of 2008. After thanking Lewis for his entertaining and informative account of aspects of the mortgage backed securities markets, the author goes on to cite Peter Wallison's "Dissent" to the 900‐page report compiled by the Financial Crisis Inquiry Commission as "the only plausible explanation of the crisis he has encountered." Wallison's main focus is the debasement of U.S. mortgage underwriting standards in the name of expanded home ownership that was initiated by U.S. law and policy makers, starting with President Clinton in 1992 and carried on by the Bush Administration. Along with the 31 million U.S. mortgages (or 56% of the 55 million total) that in June 2008 were classified "sub‐prime" or "Alt‐A"—with typical down payments ranging from anywhere from 0‐3%—the author identifies as the second main contributor to the crisis the "absurdly" low bank capital ratios (roughly 3% of total assets during the height of the crisis) that encouraged excessive risk‐taking throughout the system. Indeed, in what some observers have identified as a "game of bank bargains, " the low capital ratios were widely understood to be concessions by Congress and regulators to banks in return for their relaxation of lending standards—again, all in the name of expanded home ownerships. But this combination of policies, as we now know, did not end well.